The McGraw-Hill 36-Hour Course: Finance for Nonfinancial Managers - Girdharwal, Nitin (Indian Journal of Finance, 2020)
The book : The McGraw-Hill 36-Hour Course : Finance for Nonfinancial Managers is a step-by-step, easy-to-understand book on what the numbers intend to your organization and to you. The present prominent bookkeeping scandals of recent years have made one thing clear : you can't know a lot about the organization for which you work. What are the numbers and how would they influence you and your executive ? Be that as it may, who has the time ? In case you are similar to most managers, this book is designed for people interested in finance and investment. It provides an opportunity for the uninitiated readers to understand the basics of financial markets. This is a vast subject; still, efforts are made to cover the most important topic in a simplified manner to equip the readers with the fundamentals of finance. I accept that there is an extraordinary requirement for better correspondence among money related and nonfinancial experts for a better tool to help the nonfinancial managers comprehend the language of funds, and for the monetary experts to become familiar with the terms that are important for the nonfinancial managers. This book will equip non - financial professionals with the ability to understand and interpret financial information.